Cholesterol-Rich Lipid Rafts in the Cellular Membrane Play an Essential Role in Avian Reovirus Replication - Wang, Yuyang; Zhang, Yangyang; Zhang, Chengcheng; Hu, Maozhi; Yan, Qiuxiang; Zhao, Hongyan; Zhang, Xiaorong; Wu, Yantao (Frontiers in Microbiology, 2020)
Cholesterol is an essential component of lipid rafts in cellular plasma membranes. Although lipid rafts have been reported to have several functions in multiple stages of the life cycles of many different enveloped viruses, the mechanisms by which non-enveloped viruses, which lack outer lipid membranes, infect host cells remain unclear. In this study, to investigate the dependence of non-enveloped avian reovirus (ARV) infection on the integrity of cholesterol-rich membrane rafts, methyl-β-cyclodextrin (MβCD) was used to deplete cellular membrane cholesterol at the ARV attachment, entry, and post-entry stages. Treatment with MβCD significantly inhibited ARV replication at both the entry and post-entry stages in a dose-dependent manner, but MβCD had a statistically insignificant effect when it was added at the attachment stage. Moreover, MβCD treatment markedly reduced syncytium formation, which occurs at a relatively late stage of the ARV life cycle and is involved in cell-cell transmission and release. Furthermore, the addition of exogenous cholesterol reversed the effects mentioned above. Colocalization data also showed that the ARV proteins σC, μNS, and p10 prefer to localize to cholesterol-rich lipid raft regions during ARV infection. Altogether, these results suggest that cellular cholesterol in lipid rafts plays a critical role in ARV replication.